Implementation of The Main Distribution Material Inventory Control Policy (MDU) Using The Continuous Review Method at PT PLN (Persero) Up3 Sukabumi - Satria Achmad Hazim; Niniet Indah Arvitrida (Journal of Social Research, 2025)
The electricity industry is a strategic sector in the Indonesian economy, with PT PLN (Persero) as the main company responsible for the distribution of electrical energy. UP3 Sukabumi serves 54,636 New Install (PB) customers and 26,744 Power Change (PD) customers during the 2022-2023 period. The achievement of the lowest Service Quality Level (TMP) was due to the unavailability of Main Distribution Materials (MDU) by 46%. This study aims to optimize the control of MDU inventory using the Continuous Review (s,S) method with a Monte Carlo simulation approach. The classification of materials based on ADI-CV shows smooth and erratic characteristics with an ADI value of < 1.32. The results showed an increase in service level from 78-94% to 82-97% and a decrease in total inventory costs in 9 out of 10 materials studied. The optimal parameters obtained for MCB 25A material are s = 65 and S = 150 with a service level of 96%. The implementation of this method has a positive impact in the form of improving customer service, inventory cost efficiency, and achieving the company's TMP targets.